TEACHER AND GUIDED MULTIPLE PEER REVIEWERS IN ENHANCING EFL STUDENTSâ WRITING: A PROPOSED STRATEGY - Donasari, Renita (Lingua Scientia, 2016)
Feedback is needed in writing since feedback informs learners about their actual state of learning performance through offering guidance on the knowledge that they seize (Narciss, 2008 and Bijami et.al, 2013). Traditionally, feedback performs the role of teacher to help students improving their writing. Since, it takes time and class size constraint into consideration and alters the writing approach from product into process; peer feedback takes an essential part in writing. This study proposes âTeacher and Guided Multiple Peer Reviewers in Enhancing EFL Studentsâ Writing as there were some researches complaining that peer review may fail to identify some of the mistakes. Therefore, I propose multiple peer reviewers that will work in each stage. The frst stage (1st reviewer) will deal with unifed, well-developed, and coherent paragraph. Next, the second stage (2nd reviewer) will deal with sentences problem and pictures use and the third stage (3rd reviewer) will concern on the pattern of paragraph. The students will obtain teacher feedback after they have seen three peer reviewers. The feedback given focus on two sides; criterion-based and reader-based feedbacks to reduce studentsâ anxiety since both of criteria support each other. The feedbacks clarify how well studentsâ work meets the criteria on scoring rubric while they also will get a sense of how well their writing achieves the intended communicative purpose to the reader.